Teaching–Learning Methods of Media Literacy Education for Farhangian University Students - Parviz, Soltan; Bayani, Ali Asghar; Fakouri, Hossein; Saemi, Hassan (Assessment and Practice in Educational Sciences, 2025)
The present study aimed to identify and explain the teaching–learning methods of the media literacy education curriculum for students of Farhangian University. This study was conducted using a conventional qualitative research design. In the qualitative phase, conventional qualitative content analysis was employed to analyze semi-structured interviews and scholarly texts. The statistical population consisted of experts in the field of media literacy and teacher education, who were selected through purposive sampling. Data analysis led to the extraction of 17 concepts, 4 subcategories, and 2 main categories, including “theoretical and practical methods” and “cognitive methods.” The findings also indicated the high validity and importance of these methods in improving the process of media literacy education. In line with previous findings, the results suggest that curriculum planners and teacher educators should use a combination of theoretical, practical, cognitive, and participatory methods in media literacy education to provide a deeper, more critical, and more sustainable learning experience for students.